A monolithic integration of robust, water-/oil-repellent layer onto multilayer encapsulation films for organic electronic devices1. Issue 84 (16th September 2015) - Kim, Shin Young; Kim, Bong Jun; Kim, Do Heung; Im, Sung Gap
<x xml:space="preserve">Abstract</x> Robust, water-/oil-repellent layer is monolithically integrated onto thin film multilayer encapsulation for organic electronic devices.